Pengaruh Fasilitas Wisata Terhadap Tingkat Kepuasan Pengunjung di Desa Wisata Penglipuran Kabupaten Bangli, Provinsi Bali - Zahra, Masitha; Oktovianus, Oktovianus; Amrullah, Amrullah (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2096, 2026)
This study aims to analyze the influence of tourism facilities on visitor satisfaction at Penglipuran Tourism Village, Bangli Regency, Bali Province. The research method used is a quantitative approach with descriptive and associative analysis. Data collection was conducted through questionnaires distributed to 100 respondents who visited Penglipuran Tourism Village. The data were analyzed using validity test, reliability test, coefficient of determination, and multiple linear regression analysis with SPSS. The results show that tourism facilities, including primary and supporting facilities, are categorized as very good with an average score of 4.3. Visitor satisfaction is also in the very good category, influenced by factors such as cleanliness, comfort, and the friendliness of the local community. The analysis indicates that tourism facilities have a significant effect on visitor satisfaction, contributing 86.1%. This implies that better facilities lead to higher visitor satisfaction levels. In conclusion, tourism facilities play a crucial role in enhancing visitor satisfaction. Therefore, it is recommended that the management continuously improve facility quality, enhance accessibility, and conduct regular evaluations to provide better tourism experiences.   Keywords : tourism facilities, visitor satisfaction, tourism village, tourism, Penglipuran